Determination of Total Protein and Fatty Acid Composition of Soybean Seed as Affected by Sowing Dates - KARAASLAN, DAVUT (Asian Journal of Chemistry, 2010)
The effect of sowing dates and cultivars on total protein, oil and fatty acid composition of soybean seeds grown in southeast Anatolia region was studied. Protein content of soybean varied from 29.26 to 34.94 % and the total oil content of soybean varied from 18.61 to 19.64 %. The protein and oil contents were significantly different among treatments (p < 0.001). Sowing dates affected protein, oil, palmitic, stearic, oleic, linoleic and linolenic acids significantly (p < 0.001). Palmitic acid varied from 10.64 to 12.92 %, stearic acid varied from 4.01 to 5.17 %, oleic acid varied from 25.27 to 30.09 %, linoleic acid varied from 47.61 to 51.65 % and linolenic acid varied from 5.38 to 7.61 %, respectively. Correlation coefficients between protein and oil content were -0.2170. Sowing dates and sowing dates x cultivars interaction effects were also found to be significant (p < 0.001) over the oleic and linoleic acid contents.